Si diffusion behavior during laser welding-brazing of Al alloy and Ti alloy with Al-12Si filler wire - 陈树海 李俐群 陈彦宾 刘德健 (Transactions of Nonferrous Metals Society of China, 2010)
In laser welding-brazing of Al alloy （5A06） and Ti alloy （Ti-6Al-4V） with rectangular CO2 laser spot and with Al-12Si filler wire, element Si enriches at the interface between Ti substrate and the filler metal. It is found that the Si diffusion behavior has a significant effect on the formation of interfacial intermetallic compounds. To analyze the Si diffusion behavior, a model for the prediction of the chemical potential for ternary alloy was established. According to the calculated results of the influence of the element content and temperature in Ti-Al-Si system on Si chemical potential, the diffusion behavior of Si element was analyzed for Ti dissolution and melting mode, which presents a good agreement with the experimental data. Further, formation mechanism of the interracial inter~netllic compound was clarified.